2016
DOI: 10.1002/icd.1971
|View full text |Cite
|
Sign up to set email alerts
|

Infant Predictors of Toddler Effortful Control: A Multi-method Developmentally Sensitive Approach

Abstract: Effortful control (EC) is a form of self-regulation characterized by inhibition of dominant responses in favour of more adaptive subdominant responses. In the present study, temperamental antecedents in infancy were examined in relationship to toddler EC. Parents reported on infant temperament at 6, 8, 10, and 12 months, using the regulatory capacity/orienting (RCO) factor of the Infant Behavior Questionnaire-Revised. Laboratory indicators of this temperamental construct were also collected at each time point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Furthermore, some studies have demonstrated low convergence between commonly used measures of infant attention [ 52 , 102 , 103 ]. In our sample, we also found generally low convergence between our selected measures of infant attention ( Figure 2 ), especially across different modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have demonstrated low convergence between commonly used measures of infant attention [ 52 , 102 , 103 ]. In our sample, we also found generally low convergence between our selected measures of infant attention ( Figure 2 ), especially across different modalities.…”
Section: Discussionmentioning
confidence: 99%
“…First, several studies using parent-report measures of infant temperament have observed overall modest age-related increases in both negative and positive emotional reactivity, with accompanying decreases in RCO ability over the course of infancy (Braungart-Rieker, Hill-Soderlund, & Karrass, 2010; Costa & Figueiredo, 2011; Gartstein & Rothbart, 2003; Holmboe, Nemoda, Fearon, Sasvari-Szekely, & Johnson, 2011; Mink, Henning, & Aschersleben, 2013). Second, previous longitudinal studies that fit linear growth models to parent-report temperament data observed significant residual variability in both intercept and slope (e.g., Bridgett et al, 2009; Erickson, Gartstein, & Beauchaine, 2017; Gartstein et al, 2010), suggesting that developmental patterns of temperament could be better modeled by allowing for more than one trajectory. Because change and stability are both expected developmental patterns, we anticipated that the majority of infants follow pathways characterized by modest change, whereas smaller subsets of infants follow trajectories with more dramatic change over time (Janson & Mathiesen, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…In study 1, infants provided a saliva sample at 5 months of age for analysis of individual differences in the oxytocinergic system and underwent EEG while listening to human vocalizations at 8 months of age for the assessment of brain signal variability. Infant behavior was assessed using the Revised Infant Behavior Questionnaire (IBQ-R), a widely used and validated measure of 14 domains of infant behavior and temperament based on parental report [ 35 ] that has been shown to correlate with overt behaviors [ 36 38 ] and to prospectively predict the development of subsequent traits [ 39 42 ]. In study 2, 4-month-old infants provided a saliva sample for analysis of individual differences in the oxytocinergic system and underwent EEG while viewing faces and objects and listening to human speech and water sounds.…”
Section: Introductionmentioning
confidence: 99%